Always watch out for the flying potato salad! - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2017)
While accompanying his mother at the deli, Hank suffers a series of embarrassing accidents that cause teachers visiting the deli to go hungry, a situation that compels him to express his appreciation for his teachers' hard work.